Rethinking gender and waste: exploratory findings from participatory action research in Brazil. (1st December 2015) - ,; ,
Abstract : This article focuses on how women waste pickers identify and deal with hierarchical gender relations. Based on findings from an exploratory participatory research action project with women waste pickers in Minas Gerais, Brazil, it reflects on the different forms of oppression experienced by women waste pickers at home, in the workplace and in their national movement. The article seeks to highlight how shared reflections on particular experiences of oppression not only help build awareness of women's multiple and intersectional identities but also foster paths towards individual and collective empowerment.